Study of Electronic and Transport Properties in Double-Barrier Resonant Tunneling Systems (2022)
ABSTRACT: Resonant tunneling devices are still under study today due to their multiple applications in optoelectronics or logic circuits. In this work, we review an out-of-equilibrium GaAs/AlGaAs double-barrier resonant tunneling diode system, including the effect of donor density and external potentials in a self-consistent way. The calculation method uses the finite-element approach and the Landauer formalism. Quasi-stationary states, transmission probability, current density, cut-off frequency, and conductance are discussed considering variations in the donor density and the width of the central well. For all arrangements, the appearance of negative differential resistance (NDR) is evident, which is a fundamental characteristic of practical applications in devices. Finally, a comparison of the simulation with an experimental double-barrier system based on InGaAs with AlAs barriers reported in the literature has been obtained, evidencing the position and magnitude of the resonance peak in the current correctly.